2016
DOI: 10.2337/dc16-0413
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Considerations for Metabolic Surgery

Abstract: Obesity and diabetes represent twin health concerns in the developed world. Metabolic surgery has emerged as an established and enduring treatment for both obesity and diabetes. As the burden of obesity and diabetes varies upon the basis of ethnicity, it is also apparent that there may be differences for indications and outcomes for different ethnic groups after metabolic surgery. Whereas there appears to be evidence for variation in weight loss and complications for different ethnic groups, comorbidity remiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…the risks of particular interventions and certainly reducing the effectiveness of knowledge translation [43]. Research may wish to assess the role of race/ethnicity when considering the effectiveness of anesthesia interventions during metabolic and vitreoretinal procedures in particular, given recent findings of racial/ethnic differences in clinical presentation and outcomes [14,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the risks of particular interventions and certainly reducing the effectiveness of knowledge translation [43]. Research may wish to assess the role of race/ethnicity when considering the effectiveness of anesthesia interventions during metabolic and vitreoretinal procedures in particular, given recent findings of racial/ethnic differences in clinical presentation and outcomes [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Health-related equity characteristics are increasingly being investigated in perioperative care [10][11][12][13][14][15][16]. These characteristics may be particularly relevant in anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term follow-up and further research is required to better understand the mechanisms by which metabolic surgery improves type 2 diabetes and the shortterm and long-term benefits and risks of this procedure in youth. Quality of life and economic (cost-benefit) analyses will also be important components of ongoing follow-up and research (146,147).…”
Section: Metabolic Surgerymentioning
confidence: 99%
“…While socioeconomic factors and racial and ethnic differences may intertwine to influence access to bariatric surgery, it appears that the effect of surgery on obesity co-morbidity resolution may not be influenced by race and ethnicity, especially in the remission of type II diabetes where bariatric surgery leads to high remission across all racial and ethnic groups [85•, 86]. It is important, however, to note that in a retrospective study, Istfan N. found that all racial and ethnic groups had a decrease in hemoglobin A1c after Roux-en-Y gastric bypass, but there was a significant increase in the hemoglobin A1c levels of African Americans at 2 year follow-up, while these levels remained stable in Hispanic and white patients [87••].…”
Section: Introductionmentioning
confidence: 99%
“…Race and ethnicity seem to have less of an influence in adolescent surgical patients. In the Bariatric Outcomes Longitudinal Database, which followed 827 adolescents who underwent weight loss surgery, the mean estimated weight loss for all ethnic groups differed by a maximum of only 1.5 kg [86]. Surgery type may have an influence on whether or not race and ethnicity are determinants of weight loss as evidenced by work done by Coleman KJ and colleagues who created a registry system, which was used to track the progress of both Roux-en-y gastric bypass and sleeve gastrectomy patients.…”
Section: Introductionmentioning
confidence: 99%